2021
DOI: 10.1186/s12955-021-01898-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the validity and psychometric properties of the electronic EQ-5D-5L in routine clinical practice

Abstract: Background Electronic measurement of health-related quality of life (HRQOL) may facilitate timely and regular assessments in routine clinical practice. This study evaluated the validity and psychometric properties of an electronic version of the EQ-5D-5L (e-EQ-5D-5L) in Chinese patients with chronic knee and/or back problems. Methods 151 Chinese subjects completed an electronic version of the Chinese (Hong Kong) EQ-5D-5L when they attended a prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…An electronic version (e-EQ-5D-5L) is available and has been used in many HRQOL outcome studies [ 16 19 ]. Our previous study confirmed the validity, reliability and responsiveness of the e-EQ-5D-5L in Chinese primary care patients in Hong Kong [ 20 ]. Research supports that e-EQ-5D-5L measures in clinical practice identify more HRQOL problems and result in more actions by clinicians to tackle them [ 21 ].…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…An electronic version (e-EQ-5D-5L) is available and has been used in many HRQOL outcome studies [ 16 19 ]. Our previous study confirmed the validity, reliability and responsiveness of the e-EQ-5D-5L in Chinese primary care patients in Hong Kong [ 20 ]. Research supports that e-EQ-5D-5L measures in clinical practice identify more HRQOL problems and result in more actions by clinicians to tackle them [ 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…This study is part of a larger single-blind cluster randomized controlled trial (RCT) to evaluate the effectiveness of measuring and reporting HRQOL in routine clinical practice and the protocol has been published [ 20 ]. All doctors from three public primary care clinics that implement routine measurement of HRQOL by an e-EQ-5D-5L were invited to participate and signed a consent form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EQ-5D-5L questionnaire is available in various modes of administration, including smartphones [13]. Several studies have used the electronic version of the EQ-5D-5L questionnaire and indicated the electronic version valid and reliable [10,[14][15][16]. However, the Q1.6 mobile app of the EQ-5D-5L is designed to reduce the response burden of questionnaires by presenting a single question at a time and only querying 2 questions a day rather than the whole questionnaire at once.…”
Section: Introductionmentioning
confidence: 99%